Spectrum Sensing Algorithms for Cooperative Cognitive Radio Networks - Hassan, Yasmin Adel (2010)
A Master of Science Thesis in Electrical Engineering Submitted by Yasmin Adel Hassan Entitled, "Spectrum Sensing Algorithms for Cooperative Cognitive Radio Networks," May 2010. Available are both Soft and Hard Copies of the Thesis.